Advances in taxation. Volume 24 - Hasseldine, John (Emerald Publishing Limited, 2017)
Volume 24 of Advances in Taxation contains seven articles, covering topics such as the impact of FASB Financial Interpretation No. 48 adoption through the lens of debt covenants; conflicting results in two prior studies on the relation between aggressive financial reporting and tax reporting; how a firm's external environment affects its tax avoidance activities; and bonus depreciation. Other articles use a behavioral research methodology to explore generational values and attitudes towards tax fairness and tax compliance; the expectation gap between tax clients' motivations to hire tax preparers versus tax preparers' perceptions of those clients' motivations; and evidence on the level and determinants of corporate income tax compliance costs.
Prelims -- Market response to FIN 48 Adoption: a debt covenant theory -- Reconciling the conflicting results of prior research on the relation between aggressive book and tax reporting -- Environmental uncertainty and tax avoidance -- Impact of bonus depreciation on capital expenditures -- Generational differences in perceptions of tax fairness and attitudes towards compliance -- Demand for tax-preparation services: an exploratory examination of client versus tax-preparer expectation gaps -- Corporate income tax compliance costs and their determinants: evidence from Greece -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Taxation -- United States; Taxation; Business & Economics -- Finance -- General; Finance